Widening Scripts Cultivating Feminist Care in Academic Labor - Prandini Assis, Mariana (punctum books, 2023)
Widening Scripts: Cultivating Feminist Care in Academic Labor is addressed to scholars, educators, and students devoted to the struggle against precarity, atomization, and the commodification of knowledge. Through shared reading, discussion, and reflection, and gathered around a shared interest in feminist theory and politics, the authors discovered a model of care within academia that helped them to sustain their opposition to dominant academic practices that are diminishing, competitive, and exploitative. In this book, the authors narrate that discovery and the realization of a desire to share in the assembling of a collective feminist survival kit. In Living a Feminist Life, Sara Ahmed offers a wide-ranging killjoy survival kit that includes books, things, tools, time, life, permission notes, other killjoys, humor, feelings, and bodies. As a response to the stress, strain, and profound grief produced by the COVID-19 pandemic, with its viral acceleration of crises already endemic to neoliberal capitalism, the authors mined an evolving cluster of decolonial feminist texts in an attempt to find meaning, encounter moving premonitions, and engage with radical instigations to thought. By co-creating a survival kit through sustained collaboration during the pandemic, they develop a sense of the value of experimentation and risk-taking and learn how to cultivate an inclusive space that allows them to express their views, reclaim accountability, and learn confidently from each other. Widening Scripts combines collaborative feminist theory, acts of care, and critical dialogue in an effort to open up decelerated, altruistic, and connected ways of doing academic work together.